KONDISI RUANG PENGOLAHAN DAN KETERSEDIAAN PERALATAN KERJA REKAM MEDIS TERHADAP KINERJA PETUGAS REKAM MEDIS DI RSUD DR. ADNAAN WD PAYAKUMBUH - Darwel Elsa Mardalinda (Menara Ilmu, 2016)
Implementation of medical record quality and effectively supported by the existence ofadequate facilities, including spacious, temperature, room lighting, and the availability of workequipment. The purpose of this study was to determine the analysis of the condition of theprocessing room and availability equipment work to performance officer medical records inDr. Adnaan WD Payakumbuh Hospital. This is a descriptive study was conducted at Dr.Adnaan WD Payakumbuh Hospital on April and May 2015. The population in this study wereall file inpatients in February 2015 amounted to 704 files with a sample of 88 files, and thetechnique is systematic random sampling. Data collection is done by measuring the spacious,temperature, lighting of medical records room, observations of medical records and data filesin the univariate analysis. The results showed that the area of the processing room is notstandardized with 7.5 m x 10.5 m, storage room is standardized with 4.5 mx 10 m, thetemperature is not standardized too with 27-290C and 28-300C, lighting 51-61 lux issubstandard (300 lux). A small proportion (37.5%) is still the equipment that is not available inthe medical record file storage room, the performance of officers there were not good at45.5%. To the hospital to be able to adjust the area of the room medical records with thenumber of officers that an officer can work freely, adding that the temperature of the room airconditioner according to the ideal temperature 24-260C and add lights in each room to getstandard of illumination of 300 lux.Keywords: processing space conditions, equipment availability, performance officer